Sustain development – the first bridge of M. Lutoslawski in Lublin - Karaś, Sławomir; Skoczylas, Olga (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article was taken a technical problem of human-technical heritage. The thing applies to the 1st M. Lutoslawski’s bridge in Lublin. Years of neglect caused by a deficiency of knowledge about the bridge worth, its uniqueness meant that the structure is close to the limit condition in the sense of technical standards. This does not mean that at any moment the bridge will collapse, but each subsequent year of its duration is a further development of corrosion and cost increases of future repair. In terms of sustainable development - should endeavor not to impoverish future generations of unique monument.